Analysis of the Status Quo of Employment and Entrepreneurship of College Students in the New Era Based on Big Data Analysis and Discussion. Issue 3 (October 2020) - Guo, Shasha
Abstract: With the continuous development of China's social economy, the social demand for talent is increasing but due to the fierce competition between the markets, it also brings many problems for many college students' employment and entrepreneurship. Employment and entrepreneurship of college students have become serious. Based on this, this article first analyzes the current situation of college students' employment and entrepreneurship in the new era based on big data analysis, and then conducts an in-depth discussion on the development path of college students in the new era of employment and entrepreneurship.